Glycosylation affects ligand binding and function of the activating natural killer cell receptor 2B4 (CD244) protein - Margraf-Schönfeld, Stefanie; Böhm, Carolin; Watzl, Carsten (The journal of biological chemistry, 2011)
2B4 (CD244) is an important activating receptor for the regulation of natural killer (NK) cell responses. Here we show that 2B4 is heavily and differentially glycosylated in primary human NK cells and NK cell lines. The differential glycosylation could be attributed to sialic acid residues on N- and O-linked carbohydrates. Using a recombinant fusion protein of the extracellular domain of 2B4, we demonstrate that N-linked glycosylation of 2B4 is essential for the binding to its ligand CD48. In contrast, sialylation of 2B4 has a negative impact on ligand binding, as the interaction between 2B4 and CD48 is increased after the removal of sialic acids. This was confirmed in a functional assay system, where the desialylation of NK cells or the inhibition of O-linked glycosylation resulted in increased 2B4-mediated lysis of CD48-expressing tumor target cells. These data demonstrate that glycosylation has an important impact on 2B4-mediated NK cell function and suggest that regulated changes in glycosylation during NK cell development and activation might be involved in the regulation of NK cell responses.
Available online 23 May 2011, version of record 4 January 2021
Gesehen am 10.08.2022